Decreased Expression of CD69 on T Cells in Tuberculosis Infection Resisters - Chen, Zhen-Yan; Wang, Lei; Gu, Ling; Qu, Rong; Lowrie, Douglas B.; Hu, Zhidong; Sha, Wei; Fan, Xiao-Yong (Frontiers in Microbiology, 2020)
Background CD69 is a biomarker of T-cell activation status, but its activation status in human Mycobacterium tuberculosis (Mtb) infection remains elusive. Methods A set of cohorts of patients with different tuberculosis (TB) infection status including active TB patients (ATB), latent tuberculous infection patients (LTBI) and close contacts (CCs) of ATB was designed, and the expression profiles of CD69 and several T-cell markers were determined on Mtb antigen-stimulated T cells by flow cytometry. Results The frequencies of CD4+ and CD8+ T cells were both comparable among Mtb-infected individuals including ATB and LTBI, which guaranteed the consistency of the background level. A t-Distributed Stochastic Neighbor Embedding (tSNE) analysis on a panel of six phenotypic markers showed a unique color map axis gated on T cells in the CCs group compared with ATB and LTBI populations. By further gating on cells positive for each individual marker and then overlaying those events on top of the tSNE plots, their distribution suggested that some markers were expressed differently in the CCs group. Further analysis showed that the expression levels of CD69 on both CD4+ and CD8+ T cells were significantly lower in the CCs group, especially in interferon-γ-responding T cells. Conclusions Our findings suggest that the T-cell activation status of CD69 is associated with Mtb infection and may have the potential to distinguish LTBI from those populations who have been exposed continuously to Mtb but have not become infected.